Dualismo pulsionale e fenomeni biologici: un parallelismo? - Gaffuri Riva, Valentino (Metapsychologica - rivista di psicanalisi freudiana, 2022)
This paper will take into consideration the dual drive theory of the second Freudian topic, characterized by Eros and Thanatos, and will build an analogy between anabolic and catabolic tendencies, highlighting how both are necessary for the existence of a biological balance inside the organism and how they act simultaneously generating something similar to «compulsive kneading», as described by Freud, and how the dismantling or prevailing of one process over the other, might provoke the disease, altering the ecological balance of the organism.